1986
DOI: 10.1016/s0735-1097(86)80354-0
|View full text |Cite
|
Sign up to set email alerts
|

Mucocutaneous lymph node syndrome (Kawasaki disease): Delayed aortic and mitral insufficiency secondary to active valvulitis

Abstract: A 2 8/12 year old girl with acute mucocutaneous lymph node syndrome (Kawasaki disease), presented 17 months later with a new onset of mitral and aortic insufficiency. Congestive heart failure rapidly developed and double valve replacement was performed. Pathologic study of the excised valve tissue disclosed active valvulitis. This is the first report of late onset aortic and mitral valvulitis associated with Kawasaki disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

1989
1989
2017
2017

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(17 citation statements)
references
References 9 publications
0
17
0
Order By: Relevance
“…Late-onset valvulitis of the mitral and aortic valves can occur very rarely and may require valve replacement. 263,287 MR that becomes severe or that persists into late phases of KD appears to occur with lower frequency and can result from persistent ischemia or, rarely, from more resistant inflammatory processes that result in fixed structural abnormalities of the valve apparatus. 287,288 This circumstance indicates more serious valvular pathology and may require surgical intervention.…”
Section: Valvular Regurgitationmentioning
confidence: 99%
See 1 more Smart Citation
“…Late-onset valvulitis of the mitral and aortic valves can occur very rarely and may require valve replacement. 263,287 MR that becomes severe or that persists into late phases of KD appears to occur with lower frequency and can result from persistent ischemia or, rarely, from more resistant inflammatory processes that result in fixed structural abnormalities of the valve apparatus. 287,288 This circumstance indicates more serious valvular pathology and may require surgical intervention.…”
Section: Valvular Regurgitationmentioning
confidence: 99%
“…263,287 MR that becomes severe or that persists into late phases of KD appears to occur with lower frequency and can result from persistent ischemia or, rarely, from more resistant inflammatory processes that result in fixed structural abnormalities of the valve apparatus. 287,288 This circumstance indicates more serious valvular pathology and may require surgical intervention.AR in KD is usually associated with aortic root dilation (as indicated by an increased aortic sinus Z score) and becomes apparent early in the course of the disease. AR is of lesser severity and appears to persist more consistently, and it is less reliably associated with other inflammatory markers.…”
mentioning
confidence: 99%
“…30 Mitral regurgitation without coronary arterial lesions may also occur during the acute or convalescent stage of Kawasaki disease, in which the histopathologic findings indicate the involvement of endocarditis and valvulitis. [31][32][33] In our patients, no signs of myocardial ischemia or infarction were detected. Endocarditis or valvulitis in Kawasaki is a potential cause of the chordal rupture.…”
Section: Causes Of the Diseasementioning
confidence: 62%
“…Other investigators have observed a much lower incidence of aortic regurgitation in the acute phase, 2 but late-onset aortic regurgitation has been reported as an exceedingly rare finding after Kawasaki disease and may be associated with the need for aortic valve replacement. 2,138,140 Approximately 4% of a consecutive series with Kawasaki disease had mild aortic regurgitation as seen by echocardiogram. 100…”
Section: Valvular Regurgitationmentioning
confidence: 99%